A Qualitative Study of Women's Recall of Content and Skills Developed in Group Prenatal and Well‐Baby Care 2 Years Later. (8th November 2018) - Hackley, Barbara; Elyachar‐Stahl, Elan; Savage, Anna K.; Stange, Mia; Hoffman, Arielle; Kavanaugh, Monica; Aviles, Melanie M.; Arévalo, Sandra; Machuca, Hildred; Shapiro, Alan
Abstract : Introduction: Group prenatal and well‐baby care is a system of health care visits that occur in a group setting. Each individual session lasts approximately 2 hours, allowing more time for education and support than can occur in an individual visit. Compared with individual care, research suggests that group care is associated with similar or better short‐term outcomes, but no studies have yet examined potential long‐term benefits beyond one year postpartum. The purpose of this qualitative descriptive study was to elicit women's recall about content covered in group prenatal and well‐baby care and whether they were or were not continuing to use skills discussed during group prenatal and well‐baby care 2 or more years after their group ended. Methods: Eligible women participated in group prenatal and/or well‐baby care between 2008 and 2012, were aged at least 18 years, and were English‐speaking. Of the 127 eligible women, 32 were reached and 17 agreed to participate. Women were interviewed on average 3 years after group prenatal or well‐baby care ended using a semistructured interview guide. Transcripts were reviewed and coded by each team member. Final codes and themes were identified using an iterative review process among the research team. Results: Three themes were identified: sustained change, transferable skills, and group as a safe haven. All women were still using strategies discussed during group and had made sustained improvements in nutrition, stress management, and/or in the quality of their interactions with their children, partner, or families. The group environment was described as a safe haven: a respectful, nonjudgmental space that allowed women to share and support each other while learning new skills. Discussion: This is the first study to document that group prenatal and well‐baby care is associated with long‐term benefits in areas not yet reported in the literature: nutrition, family communication, and parenting.